(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
The article explores the multifaceted world of translation activity, encompassing theoretical foundations, practical methodologies, and technological innovations. The author provides a detailed analysis of the specific features of various types of translation (technical, medical, literary, and interpreting), examines the key challenges faced by linguists, and offers a forecast for the development of the profession in the coming years. The paper presents an in-depth overview of translation automation tools and emphasizes the indispensable role of the human factor in interpreting complex cultural codes.